2017
DOI: 10.3390/md15060160
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Toxins of the Laurentian Great Lakes, Their Toxicological Effects, and Numerical Limits in Drinking Water

Abstract: Cyanobacteria are ubiquitous phototrophic bacteria that inhabit diverse environments across the planet. Seasonally, they dominate many eutrophic lakes impacted by excess nitrogen (N) and phosphorus (P) forming dense accumulations of biomass known as cyanobacterial harmful algal blooms or cyanoHABs. Their dominance in eutrophic lakes is attributed to a variety of unique adaptations including N and P concentrating mechanisms, N 2 fixation, colony formation that inhibits predation, vertical movement via gas vesic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 299 publications
(376 reference statements)
0
40
0
1
Order By: Relevance
“…One of the first and most widespread human acute health effects upon (accidental) ingestion and intoxication of cyanobacterial bloom material is gastrointestinal illness, often with severe inflammatory diarrhea (enterocolitis) [6,12,14,168]. In the gastrointestinal epithelial layer, which is constantly exposed to a large variety of LPSs, the expression of functional TLR4 is low [169,170].…”
Section: Table 3 Overview Of Cylindrospermopsin Effects On the Gastromentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first and most widespread human acute health effects upon (accidental) ingestion and intoxication of cyanobacterial bloom material is gastrointestinal illness, often with severe inflammatory diarrhea (enterocolitis) [6,12,14,168]. In the gastrointestinal epithelial layer, which is constantly exposed to a large variety of LPSs, the expression of functional TLR4 is low [169,170].…”
Section: Table 3 Overview Of Cylindrospermopsin Effects On the Gastromentioning
confidence: 99%
“…These groups suffer more often and from more severe enteritis, as their mucosal immune system is still under development or in a permanently inflamed state. In addition, with regard to the carcinogenic and genotoxic potential of MCs and NODs, low-level chronic exposure may contribute to colon carcinoma in later years [13,113,132,168].…”
Section: Summary and Future Research Perspectivesmentioning
confidence: 99%
“…As a result of the large number of literature reports spanning over four decades of research, it can be difficult to glean accurate information on the total number of identified MCs. The phrase 'more than 100 microcystin congeners' is still often used in the literature [12,[38][39][40][41] however estimates as high as 248 known MCs have recently been published [42]. In this review, we update this number to 279 and describe the methods by which this structural elucidation was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Among the abiotic factors, nutrients, including inorganic nitrogen (N) and phosphorus (P), temperature, and light intensity, and hydrodynamic parameters of the water body (turbidity and residue time) have been reported as the most important factors in the proliferation of cyanobacteria [2,4,6]. The availability of nutrients such as N and P is essential for the growth of cyanobacteria.…”
Section: Abiotic Factorsmentioning
confidence: 99%
“…However, these water bodies are fragile and anthropic pressures such as discharge of sewage, industrial pollutants, eroding soil, and deposition of effluents rich in nitrates and phosphorus cumulating by the tourist industry and urbanization have accelerated the rate and extent of their continuous eutrophication which has led to a loss of water quality and biodiversity. Worldwide, the massive proliferation of cyanobacterial harmful algal blooms (cyanoHABs) is among the major undesirable effects resulting of eutrophication [1][2][3][4]. To date, environmental factors identified as contributing toward their global expansion included increased nutrient inputs via anthropogenic activities and temperatures and CO 2 concentrations due to changing global climate [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%